The Effect of Company Policy, Legal Compliance, and Information Technology on Audit Report Accuracy in the Textile Industry in Tangerang - Loso Judijanto; Denari Dhahana Edtiyarsih (Westscience Press, 2024)
This study investigates the influence of company policy, legal compliance, and information technology on the timeliness of audit report submissions within the textile industry in Tangerang. Using a quantitative approach with Structural Equation Modeling (SEM-PLS), data from a sample of textile companies were analyzed using a Likert scale (1-5). The results reveal significant positive relationships between company policy, information technology, legal compliance, and audit report accuracy. Findings underscore the importance of robust governance frameworks, technological investments, and regulatory adherence in enhancing audit reporting practices. Practical implications include the development of clear policies, strategic IT investments, and rigorous compliance management to improve financial reporting transparency and operational efficiency.